Two Systems, One Concept of Comparative Analysis of Dutch Noodwer and Indonesian Forced Defense - Izzah Audina; Ifahda Pratama Hapsari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This study comparatively analyzes the concept of noodweer in Dutch criminal law and forced defense in the Indonesian Criminal Code. Using a qualitative analysis method with a normative and comparative juridical approach, this study examines the differences and similarities between the two concepts, as well as their implications in legal practice. The results show that there are significant differences in interpretation and application, although there are similarities in basic principles. The Netherlands tends to adopt a broader and more flexible interpretation of noodweer, reflecting its emphasis on individual rights. In contrast, Indonesia applies a stricter interpretation to forced defense, which can be understood as an attempt to strengthen the role of the state in conflict resolution. These differences are influenced by historical, socio-cultural factors and the development of each country's justice system. The implications are seen in law enforcement and the protection of individual rights. The Dutch approach offers greater flexibility in handling complex cases, while the Indonesian approach provides clearer guidance for law enforcement officials. The study also explores the challenges and prospects for harmonizing the concept of forced defence internationally, concluding that there are opportunities for partial convergence through the development of international minimum standards and increased knowledge exchange between countries.